Prevalensi dan Luaran Gangguan Hemodinamik Dengue Shock Syndroma pada Anak Di Departemen Anak RSUD Dr SOetomo - Fenska Seipalla; Ira Dharmawati; Sundari Indah Wiyasihati (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2020)
Abstract The prevalence of Dengue infection has increased markedly worldwide. Dengue shock syndrome (DSS) is a severe manifestation of dengue virus infection. Higher mortality of DSS was found in children. This study’s aim was to portray prevalence and hemodynamic outcome in children attending the department of pediatric in Dr. Soetomo General Hospital. A Descriptive Retrospective study of children aged <15 years old with DSS was performed and evaluated from 2013-2016. The samples were divided into 5 groups, aged <1 years old, 1-2 years old, 3-5 years old 6-11 years old and 12-15 years old. Data were taken secondarily and calculated with Microsoft Excel 2010. The most common findings were prevalence of DSS in 6-11 years old group and mortality rate in <1 years old group. This can be seen as in the hemodynamic outcome; the average HR was higher in aged group 1-2 years old while RR was higher in group under 1-year-old. Meanwhile, the average blood pressure, PP, and MAP were lower in children under 2 years old. The hemodynamic outcome varies on each group based on age. Incidence of DSS remained high in older children but mortality rates were high in younger children.